"In vitro" digestibility of some shrub species from the province of La Pampa (Semiárida, 2020)
The objective of this study was to determine the quality of shrubs grown in the S.W. of La Pampa Province, Argentina, using the "in vitro" digestibility technique. Clipping dates were: March, May, July, September, December 1987 and January, 1988. The samples were processed as described by Tilley and Terry (1963) modified by Alexander. According to the results obtained, the species included in this study were divided into 3 groups A) Eight species with high digestibility throughout the year; B) Ten species with high digestibility only during a given period, C) Ten species with low digestibility throughout the year.